Effect of plant sterols on the lipid profile of patients with hypercholesterolaemia. Randomised, experimental study - Lloret Ángeles; Galdón María P; García-Reyes Mercedes; del Campo José M; Navarro Beatriz; Andrés Fernando; López-Torres Jesús; Párraga Ignacio; Precioso Juan C; Rabanales Joseba (BMC, 2011)
Abstract Background Studies have been conducted on supplementing the daily diet with plant sterol ester-enriched milk derivatives in order to reduce LDL-cholesterol levels and, consequently, cardiovascular risk. However, clinical practice guidelines on hypercholesterolaemia state that there is not sufficient evidence to recommend their use in subjects with hypercholesterolaemia. The main objective of this study is to determine the efficacy of the intake of 2 g of plant sterol esters a day in lowering LDL-cholesterol levels in patients diagnosed with hypercholesterolaemia. The specific objectives are: 1) to quantify the efficacy of the daily intake of plant sterol esters in lowering LDL-cholesterol, total cholesterol and cardiovascular risk in patients with hypercholesterolaemia; 2) to evaluate the occurrence of adverse effects of the daily intake of plant sterol esters; 3) to identify the factors that determine a greater reduction in lipid levels in subjects receiving plant sterol ester supplements. Methods/Design Randomised, double-blind, placebo controlled experimental trial carried out at family doctors' surgeries at three health centres in the Health Area of Albacete (Spain). The study subjects will be adults diagnosed with "limit" or "defined" hypercholesterolaemia and who have LDL cholesterol levels of 130 mg/dl or over. A dairy product in the form of liquid yoghurt containing 2 g of plant sterol ester per container will be administered daily after the main meal, for a period of 24 months. The control group will receive a daily unit of yogurt not supplemented with plant sterol esters that has a similar appearance to the enriched yoghurt. The primary variable is the change in lipid profile at 1, 3, 6, 12, 18 and 24 months. The secondary variables are: change in cardiovascular risk, adherence to the dairy product, adverse effects, adherence to dietary recommendations, frequency of food consumption, basic physical examination data, health problems, lipid-lowering medication, physical activity, smoking habits and socio-demographic variables. Discussion If plant sterol ester supplements were effective a sounder recommendation for the consumption of plant sterols in subjects with hypercholesterolaemia could be made. Trial Registration Current Controlled Trials NCT01406106.